Mesenchymal Stem Cell Therapies Approved by Regulatory Agencies around the World - Luis E. Fernández-Garza; Silvia A. Barrera-Barrera; Hugo A. Barrera-Saldaña (MDPI AG, 2023)
Cellular therapy has used mesenchymal stem cells (MSCs), which in cell culture are multipotent progenitors capable of producing a variety of cells limited to the mesoderm layer. There are two types of MSC sources: (1) adult MSCs, which are obtained from bone marrow, adipose tissue, peripheral blood, and dental pulp; and (2) neonatal-tissue-derived MSCs, obtained from extra-embryonic tissues such as the placenta, amnion, and umbilical cord. Until April 2023, 1120 registered clinical trials had been using MSC therapies worldwide, but there are only 12 MSC therapies that have been approved by regulatory agencies for commercialization. Nine of the twelve MSC-approved products are from Asia, with Republic of Korea being the country with the most approved therapies. In the future, MSCs will play an important role in the treatment of many diseases. However, there are many issues to deal with before their application and usage in the medical field. Some strategies have been proposed to face these problems with the hope of reaching the objective of applying these MSC therapies at optimal therapeutic levels.